Pembinaan Ibu-Ibu Rumah Tangga dalam Mengimplimentasikan Keluarga Maslahah di Jamaah Fatayat-Muslimat Ranting NU Desa Balongdowo Kecamatan Kepohbaru Kabupaten Bojonegoro - Munir Munir (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to describe the process of empowering housewives in implementing the concept of a maslahah family in the Fatayat–Muslimat Ranting NU community of Balongdowo Village, Kepohbaru District, Bojonegoro Regency. Using a Participatory Action Research (PAR) approach, this study involved the women members of Fatayat–Muslimat as active subjects in the process of problem identification, planning, action, observation, and reflection. Data were collected through in-depth interviews, participatory observation, and documentation, and were analyzed using the Miles, Huberman, and Saldaña model. The results of the study show that the empowerment program successfully increased understanding and implementation of maslahah family values, particularly in the areas of family spirituality, harmonious communication, household economic management, and child education. The PAR process encouraged behavioral changes and critical awareness among the women in managing their families more wisely and with a focus on communal welfare. This study highlights that participatory-based empowerment can be an effective strategy for strengthening families and empowering women at the community level. The results also demonstrate the significant potential of participatory approaches in enhancing family resilience and improving the quality of social life within the community.